Africa Common Position on Food Systems: A summary of the official Africa Common Position presented in September 2021 as part of the United Nations Food Systems Summit - Accelerating Impacts of CGIAR Climate Research for Africa; African Union Development Agency (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This report forms part of an AICCRA knowledge series on Food Systems. Africa presented a common position to the UNFSS, whose narrative was guided by the current challenges related to feeding the growing population amid the environmental footprint of global agriculture, worsening climate crisis, and deepening inequality amplified by the uncertainty of the COVID-19 pandemic. Informed by existing continental and regional policy frameworks and outcomes from the national dialogues on the UNFSS, the Africa common position demonstrates the continent's commitment to contributing to setting the agenda for global food systems transformation. This series of briefing notes summarises key thematic areas of the Africa Common Position.